An examination of STEAM teacher competencies - Beşkese, Münire Berna. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The purpose of this study was to investigate how STEAM teachers conceptualize, define, and actualize what it means to be a STEAM teacher. A phenomenological research which is one of the qualitative methods was followed. A literature review, field visit (to one of the best STEM schools in Istanbul) and four pilot studies were completed to design in depth, semi-structured interview questions that served the two research questions; “How do STEAM teachers conceptualize the STEAM teacher competencies?” and “How do STEAM teachers define the differences between ideal teacher competencies and STEAM teacher competencies?”. Five teachers from USA with at least two years of experience as a STEAM teacher were interviewed. Respondents’ resumes and STEAM teacher competency mind maps were used for triangulation. Hierarchical Focusing Method was followed to receive interviewees’ prominently conceptualized STEAM teacher competencies. Rapid Identification of Themes from Audio Recordings (RITA) method was utilized to capture the facial expressions and tones that reflected the sense of importance of the competency the interviewee was talking about. As a result, one hundred and thirty-nine abilities, characteristics and skills were listed as the STEAM teacher competencies and twenty eight abilities, characteristics and skills were recorded as the differences between ideal and STEAM teacher competencies. “Collaborating with Colleagues”, “Collaborating with Professionals”, “Life-long Learner”, and “Creator and Innovator” were declared the most for STEAM teacher competencies. “Integrating Concepts”, “Appreciating Arts” and “Having various Hobbies” were highly mentioned STEAM teacher competencies which ideal teachers might not necessarily possess.
Keywords: Science -- Study and teaching -- Methodology.; Interdisciplinary approach in education.; Science and the arts.